Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.6 - Rational Expressions - Exercise Set - Page 85: 54


$\displaystyle -\frac{5x}{(x-6)(x+4)(x-1)},\qquad x\neq 6,1, -4$

Work Step by Step

Factor each denominator. Factoring $x^{2}+bx+c$, we search for two factors of c (m and n) such that m+n=b. If they exist, $x^{2}+bx+c =(x+m)(x+n)$ $ x^{2}-2x-24=\quad$... we find factors $+4$ and $-6,$ $=(x+4)(x-6)$ $ x^{2}-7x+6=\quad$... we find factors $-6$ and $-1,$ $=(x-6)(x-1)$ Build the LCD by listing common factors first. Then list all the "leftover" factors. $LCD=(x-6)(x+4)(x-1)$ $\displaystyle \frac{x}{x^{2}-2x-24}-\frac{x}{x^{2}-7x+6}=\frac{x}{(x-6)(x+4)}-\frac{x}{(x-6)(x-1)}$ $=\displaystyle \frac{x}{(x-6)(x+4)}\times\frac{x-1}{x-1}-\frac{x}{(x-6)(x-1)}\times\frac{x+4}{x+4}$ $=\displaystyle \frac{x^{2}-x}{(x-6)(x+4)(x-1)}-\frac{x^{2}+4x}{(x-6)(x+4)(x-1)}$ $=\displaystyle \frac{x^{2}-x-x^{2}-4x}{(x-6)(x+4)(x-1)}$ $=\displaystyle \frac{-5x}{(x-6)(x+4)(x-1)},\qquad x\neq 6,1, -4$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.